2021
DOI: 10.1111/ijcp.14719
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Artemisia extract on glycemic control: A systematic review and meta‐analysis of randomized controlled trial

Abstract: Diabetes mellitus (DM) is a chronic metabolic disorder characterized by elevated blood glucose levels because of a lack of insulin secretion or insulin resistance. 1 Based on International Diabetes Federation reports, 415 million adult subjects have DM around the world and the trend is ascending. 2 DM complications are categorized into the micro and macro vascular damages and can affect the heart, kidney, eyes and nerves. 3 Besides critical complications, DM can cause financial burden and decrease quality of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 51 publications
0
5
1
Order By: Relevance
“…However, this study did not demonstrate a statistically significant difference in 12-week glycemic control between study groups. In their review, Sasani et al concluded that complementary therapy with different Artemisia extracts significantly improved insulin resistance (HOMA2-IR), but benefits in glycemic control remained unclear [16]. Extracts of Artemisia spp have diverse secondary metabolites [17], and the majority of the known potent anti-hyperglycemic phytochemical compounds, i.e., flavonoids, coumarins, and essential oils, are largely abundant in a few Artemisia spps like A. drancunculus and A. princeps [18].…”
Section: Discussionmentioning
confidence: 99%
“…However, this study did not demonstrate a statistically significant difference in 12-week glycemic control between study groups. In their review, Sasani et al concluded that complementary therapy with different Artemisia extracts significantly improved insulin resistance (HOMA2-IR), but benefits in glycemic control remained unclear [16]. Extracts of Artemisia spp have diverse secondary metabolites [17], and the majority of the known potent anti-hyperglycemic phytochemical compounds, i.e., flavonoids, coumarins, and essential oils, are largely abundant in a few Artemisia spps like A. drancunculus and A. princeps [18].…”
Section: Discussionmentioning
confidence: 99%
“…TA B L E 6 Appetite indices and dietary intake before and after the study clinically important. Studies of Dogan et al (Dogan et al, 2015) and Shaheen et al (Shaheen et al, 2017) reveal an improvement in levels of HDL, LDL, TC, and TG, where the higher Quercus extract doses yielded better improvements. The abovementioned studies suggested that the mechanism could be associated with the decrement in cholesterogenesis and synthesis of fatty acid, and may be related to the amelioration in glucose and insulin levels.…”
Section: Effects Of Acorn Muffin On Lipid Profilementioning
confidence: 93%
“…Further, the greater the amount of Quercus extract level, the better the observed glycemic improvement (Dogan et al, 2015). Also, Shaheen et al (Shaheen et al, 2017) reported the positive effects of the Q. dilatata extract on blood glucose levels of diabetic rats.…”
Section: Ta B L Ementioning
confidence: 97%
See 2 more Smart Citations